2000
DOI: 10.1007/s003590000136
|View full text |Cite
|
Sign up to set email alerts
|

Selective receptor neurone responses to E -β-ocimene, β-myrcene, E , E -α-farnesene and homo -farnesene in the moth Heliothis virescens , identified by gas chromatography linked to electrophysiology

Abstract: An important question in olfaction is for which odorants receptor neurones have evolved. In the present study, olfactory receptor neurones on the antennae of the tobacco budworm moth Heliothis virescens were screened for sensitivity to naturally occurring plant-produced volatiles by the use of gas chromatography linked to electrophysiology. Volatiles of host as well as non-host plants collected by headspace techniques were used for stimulating the neurones, sequentially via two columns, one polar and one nonpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2001
2001
2006
2006

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(25 citation statements)
references
References 0 publications
3
22
0
Order By: Relevance
“…Since single-cell recordings have shown similar sensitivities of the RN types to their primary odorants (Stranden et al, 2003b), the present EAG recordings may indicate that H. virescens has a higher number of RNs responding to linalool than to the other two odorants. In addition, the EAG and calcium imaging experiments showed somewhat stronger responses to β-ocimene than to β-myrcene, the two compounds known from electrophysiological recordings to activate the same RN type, β-ocimene being the primary and β-myrcene a secondary odorant (Røstelien et al, 2000b;Stranden et al, 2003b). Thus, the results of the present study may indicate that learning performance with the three odorants increases with a larger number of RNs responding and/or with a higher firing rate of the RNs.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Since single-cell recordings have shown similar sensitivities of the RN types to their primary odorants (Stranden et al, 2003b), the present EAG recordings may indicate that H. virescens has a higher number of RNs responding to linalool than to the other two odorants. In addition, the EAG and calcium imaging experiments showed somewhat stronger responses to β-ocimene than to β-myrcene, the two compounds known from electrophysiological recordings to activate the same RN type, β-ocimene being the primary and β-myrcene a secondary odorant (Røstelien et al, 2000b;Stranden et al, 2003b). Thus, the results of the present study may indicate that learning performance with the three odorants increases with a larger number of RNs responding and/or with a higher firing rate of the RNs.…”
Section: Discussionsupporting
confidence: 53%
“…Thus, the results of the present study may indicate that learning performance with the three odorants increases with a larger number of RNs responding and/or with a higher firing rate of the RNs. Electrophysiological studies have previously shown that β-ocimene and β-myrcene activate the same RN type, whereas linalool activates two other types; linalool being the primary odorant of one and a secondary odorant of the other (Røstelien et al, 2000b;Stranden et al, 2003b; T. Røstelien, M.S., A.-K. Borg-Karlson and H.M., unpublished). One would therefore expect the moths to discriminate between linalool and the two other compounds more easily than between β-ocimene and β-myrcene.…”
Section: Discussionmentioning
confidence: 94%
“…Recent behavioural studies have shown that (−)-germacrene D increases the attraction and oviposition by mated H. virescens females (Mozuraitis et al, 2002). Other studies are in progress, which will attempt to show the further behavioural significance of the electrophysiological results, including the ability to discriminate (+)-and (−)-germacrene D. Other receptor neurone types identified in heliothine moths are tuned to E,E-α-farnesene, homo-farnesene, linalool, and E-β-ocimene, showing functional similarities in the different species (Røstelien, 2000b; T. Stranden, A.-K. Borg-Karlson, H. Mustaparta, unpubl. ).…”
Section: Comparative Olfaction In Related Species Of Heliothine Mothsmentioning
confidence: 99%
“…Correlating these responses with the chromatogram obtained with FID detection reveals which compounds are perceived by the antennae. 100,[158][159][160][161][162] Advances in this methodology that allow recordings to be made inside the central nervous system in combination with the novel technique of in vivo calciumimaging have helped neurobiologists to start to understand how plant VOCs are detected and processed by insects. [163][164][165] While methods such as GC-EAD or GC-SCR might give information on whether a compound is perceived by the olfactory system of an animal, 157 only behavioural tests will show if the animals are indeed attracted or repelled by a particular compound.…”
Section: Bioassays and Bioassay-linked Hipv Analysesmentioning
confidence: 99%